A reverse localization scheme for underwater acoustic sensor networks - Moradi, Marjan (2013)
Underwater Wireless Sensor Networks (UWSNs) offer new opportunities to observe and predict the behavior of aquatic environments. A vital service in UWSNs is localization used in many underwater applications such as warning systems for natural disaster, ecological applications and military surveillance. In these applications, the locations of sensors need to be determined for meaningful interpretation of the sensed data. Localization for underwater is challenging as compared to terrestrial because the latter has stabilized in WSNs. In underwater networks, acoustic communication is a typical physical layer technology which has limitations and challenges. Moreover, there is a need for a large amount of sensor nodes to cover wide and deep (three dimensional) oceanographic regions. Consequently, it is essential to develop a localization protocol specifically for Underwater Acoustic Sensor Networks (UASNs). Unfortunately, many of the existing underwater localization schemes suffer limitations such as long localization time, low location accuracy, excessive messaging and limited power. Therefore, the aim of this research is to develop a faster localization scheme for UASN to reduce energy consumption and communication overhead, and to be adaptable to the mobility of water current and location changes. The proposed scheme is named Reverse Localization Scheme (RLS). The developed localization scheme is mathematically compared with seven efficient methods in terms of communication cost. Besides that, the RLS results are compared with the benchmark method Dive’N’Rise Localization using MATLAB. Simulation results showed that the developed scheme achieved faster localization time with the least possible message transfers. In addition, the scheme offers a real time localization and it is less susceptible to errors caused by mobile underwater currents. RLS has been proven to be power-efficient as all parts of the localization computations are computed at the onshore sink.